The effect of e-assessment on performance, competency, worklife balance, and motivation on civil servant performance - Eladira, Eladira; Lubis, Yusniar; Sakti, Indra (International Journal of Financial, Accounting, and Management, 2024)
Purpose: Lousy work by employees often leads to undesirable situations in bureaucracy. This study aims to assess the performance of civil servants employed by the Serdang Bedagai district administration regarding competency, work-life balance, motivation at work, and e-performance evaluation. Research methodology: The data gathering process involves the application of quantitative approaches. Results: The research findings show that the implementation of e-performance evaluation has a positive and significant impact on the performance of civil servants in the Serdang Bedagai Regency Government, with a significance level of 0.002 < 0.05. Additionally, competency had a positive and significant effect on the performance of civil servant employees in the Serdang Bedagai Regency Government, with a significance level of 0.000 < 0.05. Work-life balance positively and significantly affects civil servant performance in the Serdang Bedagai Regency Government, with a significance threshold of 0.020 < 0.05. Similarly, work motivation positively and significantly affects government officials' performance in the Serdang Bedagai Regency Government, at a significance level of 0.000 < 0.05. The concurrent implementation of e-performance evaluation, competency, work-life balance, and work motivation has been found to significantly impact the performance of civil servant personnel in the Serdang Bedagai Regency Government, with a significance level of 0.000 < 0.05. Limitations: The research problem only focuses on four variables; therefore, expanding the research to other variables is necessary.   Contribution:  This research will provide evidence that several sectors must be considered in government bureaucracy. Novelty: All research variables influence civil servants in Serdang Bedagai.